Digital Transformation of SMEs: Boosting Online Shopping Interest through E-Commerce Adoption - Apriani, Ari; Wahdiniawati, Siti Annisa; Perkasa, Didin Hikmah; Magita, Magita; Meliantari, Dian; Widayati, Catur (Dinasti International Journal of Digital Business Management, 2024)
The purpose of this study is to provide advice to conventional small and medium-sized businesses (SMEs) that want to increase their income by implementing online sales and marketing strategies. The necessity for SMEs to use e-commerce as a sales and marketing channel amid the COVID-19 epidemic is what spurred this inquiry. The use of e-commerce is seen as crucial by SME practitioners owing to its user-friendly transaction procedures and perceived safety. Customers who use platforms like Shopee and Tokopedia and who live in the Jakarta, Bogor, Depok, Tangerang, and Bekasi districts are the focus of the study. A questionnaire was used to poll 189 people in these locations as a sample. Partial Least Squares (PLS) were used to do quantitative analysis. According to the study's findings, consumers' intentions to make online purchases are not significantly impacted by perceived usefulness, perceived ease of use, or perceived risk. On the other hand, buying online intentions are significantly influenced by perceived enjoyment and trust. These results imply that in developing e-commerce platforms and marketing strategies, there should be a focus on fostering consumer trust, delivering enjoyable experiences, and ensuring ease of use and perceived benefits for users.